Imagination and Science in Romanticism. - Joiner, Jorunn (Journal for Eighteenth-Century Studies, 2023)
Fulfilling the aim "to restore connections between Romantic literature and science", Sha shows that imagination was as vital for poetic composition as it was for scientific experimentation (p. 1). Sha is careful not to dismiss the Romantic desire for unity and form; instead, he incorporates these urges as a shared project between Romantic science and art as they investigate the experience of being. As university cuts in arts funding are contrasted against expanding science programmes, and with the advent of AI algorithms composing poetry, recognizing that science and art can develop symbiotically is as timely as it is important.